1993
DOI: 10.1523/jneurosci.13-05-02001.1993
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of phosphoinositide-linked metabotropic glutamate receptor (mGluR1) and the inositol 1,4,5-trisphosphate receptor in rat brain

Abstract: The type 1 metabotropic glutamate receptor (mGluR1) is through to act via the phosphoinositide (PI) system with the associated formation of inositol 1,4,5-trisphosphate (IP3) and Ca2+ release. Utilizing immunohistochemistry and in situ hybridization, we have localized protein and mRNA, respectively, for the mGluR1 and the IP3 receptor (IP3R). We have also localized glutamate-linked PI turnover by autoradiography with 3H-cytidine. We observe a striking contrast in localizations of mGluR1 and IP3R both for prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
138
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 46 publications
19
138
3
Order By: Relevance
“…Of these, glutamate receptor agonists have been shown to stimulate phosphoinositide turnover in cells expressing mGluRla/,B and mGluR5 (Abe et al, 1992;Tanabe et al, 1992;Pickering et al, 1993). The mGluRs linked to phosphoinositide turnover exhibit pharmacological differences (Abe et al, 1992;Aramori & Nakanishi, 1992;Tanabe et al, 1992;Pickering et al, 1993), differential susceptibility to pertussis toxin (Abe et al, 1992;Aramori & Nakanishi, 1992;Pickering et al, 1993) and have been shown to be differentially expressed in rat brain (Abe et al, 1992;Martin et al, 1992;Fotuhi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, glutamate receptor agonists have been shown to stimulate phosphoinositide turnover in cells expressing mGluRla/,B and mGluR5 (Abe et al, 1992;Tanabe et al, 1992;Pickering et al, 1993). The mGluRs linked to phosphoinositide turnover exhibit pharmacological differences (Abe et al, 1992;Aramori & Nakanishi, 1992;Tanabe et al, 1992;Pickering et al, 1993), differential susceptibility to pertussis toxin (Abe et al, 1992;Aramori & Nakanishi, 1992;Pickering et al, 1993) and have been shown to be differentially expressed in rat brain (Abe et al, 1992;Martin et al, 1992;Fotuhi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Group II (mGluRs 2 and 3) and group III (mGluRs 4 -8) receptors inhibit adenylyl cyclase, although with different pharmacological profiles (for review, see Pin and Duvosin, 1995;Roberts, 1995). Ligand-binding studies have shown the striatum to possess a high density of mGluR binding sites (Albin et al, 1992), and several mGluR mRNAs and proteins are expressed by striatal neurons, including members of all three mGluR groups (Abe et al, 1992;Martin et al, 1992;Shigemoto et al, 1992Shigemoto et al, , 1993Fotuhi et al, 1993;Ohishi et al, 1993a,b;Saugstead et al, 1994;Testa et al, 1994;Joly et al, 1995;Romano et al, 1995).…”
Section: Abstract: Metabotropic Glutamate Receptor; Basal Ganglia; Smentioning
confidence: 99%
“…Significant differences between drug treatments within each region were determined with 95% confidence intervals. Additional comparisons were made by determining the relative glucose utilization in each region as a ratio of the 14 C concentration of the region to the mean 14 C concentration of whole brain uptake for that animal (relative 2-deoxyglucose uptake) (Mitchell and Crossman, 1984;Sharp et al, 1993;Trugman and James, 1993). The ratio of region/whole brain uptake could then be used for comparisons with Student's t tests.…”
Section: Drugsmentioning
confidence: 99%
“…The group 1 mGluRs consists of GluR 1 and mGluR 5 subtypes. Both are present in the medial cerebral cortex; mGluR 5 is located in all cortical layers preferentially at the postsynaptic dendritic spines (Romano et al, 1995), whereas mGluR 1 is present in layers 2/3 (Fotuhi et al, 1993). We tested the effect of CPCOOEt (100 µM), a selective antagonist of mGluR 1 , and compared it to MPEP (30 µM) the preferential mGluR 5 antagonist.…”
Section: Contribution Of Vsccsmentioning
confidence: 99%